Increased price markup from union coordination: OECD panel evidence - Roger Bjørnstad; Kjartan Øren Kalstad (Kiel Institute for the World Economy (IfW), 2010)
Although coordination of wage bargaining probably affects entry barriers and competition in product markets, research on price determination has typically not considered such factors. In this paper the price markup depends on coordination and is estimated on a panel of 15 OECD countries. The estimates show that consumer prices may be as much as 21 percent higher in coordinated compared to uncoordinated countries, solely due to the effect of coordination on the price markup. Since coordination has a dampening effect on wages, this may explain why many researchers have been unable to find any clear effect of coordination on unemployment.
Keywords: C23; E31; J51; 330; Imperfect competition model; price markup; labor market institutions; unemployment; panel data model; Tarifpolitik; Lohnverhandlungen; Wirkungsanalyse; Mark-up Pricing; Konsumgütermarketing; Arbeitslosigkeit; Panel; Schätzung; OECD-Staaten